2015
DOI: 10.1007/s10461-014-0978-6
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between ART Adherence and Smoking Status Among HIV+ Individuals

Abstract: Smoking is highly prevalent among HIV+ individuals and studies indicate that it may be associated with poor ART adherence, though the relationship is poorly understood. In addition little is known about interest in quitting among HIV+ smokers who are having adherence difficulties. We examined smoking and ART adherence among 203 HIV+ individuals enrolled in a randomized trial of interventions to increase ART adherence. Prior analyses indicated there were no overall treatment group effects. Smoking status and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
(48 reference statements)
1
9
0
Order By: Relevance
“…However, in multivariable models after adjusting for covariates, no significant associations were found between current smoking and imperfect ART adherence. Others (21, 22) have examined medication adherence and smoking in PLWH, and also have not found an association with ART adherence. It is possible that smoking and imperfect ART adherence share similar risk factors and, perhaps, smoking may be acting as a surrogate marker for these other factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in multivariable models after adjusting for covariates, no significant associations were found between current smoking and imperfect ART adherence. Others (21, 22) have examined medication adherence and smoking in PLWH, and also have not found an association with ART adherence. It is possible that smoking and imperfect ART adherence share similar risk factors and, perhaps, smoking may be acting as a surrogate marker for these other factors.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have shown that smokers have a higher prevalence of detectable HIV viral load (14, 1820), overall, research in this area has provided mixed results with regard to the association between cigarette smoking and ART adherence. For example, two studies found no association between smoking status and ART adherence (21, 22), while another found that nicotine dependence (measured by the Fagerstrom Test for Nicotine Dependence [FTND]) was significantly related to suboptimal adherence (23). Thus, there remain open questions about the associations between smoking and HIV medication adherence.…”
Section: Introductionmentioning
confidence: 99%
“…This increased susceptibility has been mainly attributed to biochemical mechanisms including the immunosuppressive effects of smoking and its negative impact on immune and virological response even when on ART 13 . Behavioural mechanisms have also been suggested—for example, an association between smoking and non-adherence to antiretroviral therapy 14, 15…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients who are co-infected with TB and HIV, and who smoke, are predisposed to many HIV-related complications [9]. In addition tobacco smoking and alcohol consumption are associated with reduced ART initiation and adherence [10,11], which also negatively influences clinical response to treatment.…”
Section: Introductionmentioning
confidence: 99%